Snacks for the soul : snacks for the soul is a collection of stories that offer emotional, intellectual and spiritual nourishment - Vaswani, J.P (Kuala Lumpur : Snergymedia, 2007)
Snack for the soul is a collection of stories that offer emotional, intellectual and spiritual nourishment
Keywords: Conduct of life; Life skills; Self-actualization (psychology) -- Buddhism; Spiritual life -- Buddhism